PERFORMA PERTUMBUHAN UDANG VANAME (Litopenaeus vannamei) PADA INDUSTRI TAMBAK UDANG PT. BERKAT KASIH KARUNIA TAPANULI TENGAH DITINJAU DARI ASPEK KUALITAS AIR - Hutabarat, Muharriswan; Samiaji, Joko; Rumondang, Anne (Jurnal Perikanan Terapan, 2025)
Vannamei shrimp (Litopenaeus vannamei) has become a national flagship commodity from the aquaculture sector, because it has wide market opportunities, both domestically and abroad. Vannamei shrimp cultivation in Central Tapanuli Regency has begun to be carried out and has developed quite rapidly since the last few years. The purpose of the study is to determine the influence of water quality on the growth of vannamei shrimp in the shrimp pond industry of PT. Berkat Kasih Karunia in Central Tapanuli Regency, analyzed environmental factors that affect the survival rate (SR) of vannamei shrimp and to identify water quality parameters that affect the growth of vannamei shrimp in shrimp ponds of PT. Berkat Kasih Karunia. The method used in this study is a descriptive method. A number of the parameters measured include absolute weight growth and absolute length, survival (SR), water quality in the form of temperature, pH, DO, brightness and salinity. The results showed thant for the growth in weight ranging from 8,0 – 8,3 g and in length between 6,5 – 6,8 cm, respectively, in which considered optimal under the condition of maintained water quality. The water quality ranged as foloow: temperature 28,9–29,0 0C, pH 7,5-7,7, dissolved oxygen (DO) 5,8-6,1 (mg/l), brightness 38,4-39,0 cm, and salinity 19,5-20,0 ppt. This range of parameters supported the physiological activity of the shrimp, and the absolute growth of vannamei shrimp during the study. The survival rate (SR) of vannamei shrimp of 98% indicates the success of pond water quality management. It also indicates that the pond environment is free from the excessive environmental stress, such as extreme salinity, low oxygen, or phatogenic attack.